From second to hundredth opinion in medicine: A global consultation platform for physicians. Issue 1 (December 2018) - Muse, Evan; Godino, Job; Netting, Jessa; Alexander, James; Moran, Helen; Topol, Eric
Abstract Serious medical diagnostic errors lead to adverse patient outcomes and increased healthcare costs. The use of virtual online consultation platforms may lead to better-informed physicians and reduce the incidence of diagnostic errors. Our aim was to assess the usage characteristics of an online, physician-to-physician, no-cost, medical consultation platform, Medscape Consult, from November 2015 through October 2017. Physicians creating original content were noted as "presenters" and those following up as "responders". During the study period, 37, 706 physician users generated a combined 117, 346 presentations and responses. The physicians had an average age of 56 years and were from 171 countries on every continent. Over 90% of all presentations received responses with the median time to first response of 1.5 h. Overall, computer- and device-based medical consultation has the capacity to rapidly reach a global medical community and may play a role in the reduction of diagnostic errors.